Severity of Depression in Mothers of children suffering from Cerebral Palsy - Ayesha Goheir, Alamzeb Jadoon, Syeda Shazmina Fayyaz, Nazma Kiran, Naveed Akhtar, Zia Qamar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cerebral palsy (CP) is the most common cause of motor disability in children with worldwide having incidence of 2 per 1000 live births. Children with CP have motor disability, decreased ability to walk, poor feeding and limited exposure to sunlight. Malnutrition, behavior challenges and motor deficits in CP children are common causes of depression in their mothers. Aim: The present study focused to estimate the severity of depression in mothers, looking after the children suffering from severe CP and to compare their depression scoring with the scores of mothers having healthy children. Methods: The cross-sectional comparative study included 21 mothers having children suffering from severe CP and 21 controls (Mothers of normal children). Depression was calculated by the Beck Depression Inventory (BDI). Results: A statistically significant difference was observed between the mean scores of BDI II between the two groups Conclusion: Results revealed that mothers having CP children are more depressed than mothers having healthy children. It imitates the importance of psychiatric, social and family support to mother along with the treatment of the child. Keywords: CP, depression, BDI II.